THE INFLUENCE OF CAR, ROA, FDR ON MURABAHAH FINANCING WITH NPF AS MODERATING VARIABLE - Alwi Zaenudin; Nila Saadati (Journal of Applied Economics in Developing Countries, 2023)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Third Party Funding (TPF), Return on Assets (ROA), and Financing Deposit Ratio (FDR) on murabahah financing with Non Performing Financing (NPF) as a moderating variable. This study uses quantitative types using purposive sampling techniques by setting several criteria so that 50 observations and 10 Full-Fledged Islamic Banks are the research sample. This research uses secondary data from panel data at Full-Fledged Islamic Banks for 2018-2022. The results of this study show that: 1) The Capital Adequacy Ratio (CAR) has no effect and negatively impacts murabahah financing; 2) Third Party Funding (TPF) has a positive and significant effect on murabahah financing; 3) Return On Assets (ROA) has a positive and significant effect on murabahah financing; 4) Financing To Deposit Ratio (FDR) has no effect and negatively impacts murabahah financing; 5) Non-performing financing (NPF) cannot moderate the influence of the Capital Adequacy Ratio on murabahah financing; 6) Non-performing financing (NPF) can moderate the influence of Third party funding on murabahah financing; 7) Non-performing financing (NPF) can moderate the influence of Return On Assets on murabahah financing; and 8) Non-performing financing cannot moderate the influence of the Financing To Deposit Ratio on murabahah financing.